ANALYSIS OF THE EFFECTIVENESS OF THE EMPLOYEE WELL-BEING PROGRAM ON EMPLOYEE PERFORMANCE AT MANADO STATE POLYTECHNIC - Jufrina Mandulangi; Precylia Ribka Rambing; Lis M.Yapanto (Smart Education, 2026)
Abstract: Background: The demands of the workplace in higher education institutions, including polytechnics, require optimal performance from their human resources. Stress, burnout, and work-life imbalance can reduce productivity. The Employee Well-Being (EWB) program is designed to improve the holistic well-being (physical, mental, social, and financial) of employees. However, the program's effectiveness in boosting performance in the context of Manado State Polytechnic requires empirical study. Objective: This study aims to analyze the relationship and influence of employee perceptions on the effectiveness of the Employee Well-Being Program on their performance.Method: The study used a quantitative approach with a survey method. A sample of 50 employees (lecturers and educational staff) at Manado State Polytechnic was selected using a purposive sampling technique. Data were collected through a closed questionnaire measuring two variables: (1) Perception of the Effectiveness of the EWB Program (24 indicators including physical health, mental support, social relationships, and financial well-being) and (2) Employee Performance (10 task-based and contextual indicators). Data were analyzed statistically using the Pearson Product Moment correlation test and simple linear regression analysis.Results: The analysis results show a correlation coefficient (r) of 0.712, which indicates a strong positive relationship between the perception of the effectiveness of the EWB Program and employee performance. The R Square value (coefficient of determination) is 0.507, meaning that approximately 50.7% of the variation in employee performance can be explained by variations in their perceptions of the effectiveness of the EWB Program. The results of the regression test show the equation Y = 15.245 + 0.789X, with a significance value (p)